Festival Sea-Sea: Gastronomic creativity of coastal communities in Banggai Island - Syahrul Karim; Yusup Apriyanto; Wan Ahmad Hasni Wan Zulkifali; Gozali Gozali (Borneo Novelty Publishing, 2025)
Purpose - The purpose of this research is to explore the gastronomic creativity of coastal communities, particularly in the utilization of local ingredients from the sea and surrounding environment, as well as how they develop sustainable culinary techniques and innovations, including aspects of culinary heritage.Method/Approach/Design - This research adopts a qualitative approach with a case study of the Festival Sea-Sea. Data were collected through interviews with local culinary practitioners and observations of festival activities, such as cooking demonstrations and discussions on sustainability in gastronomy.Findings - The research finds that coastal communities combine culinary innovation with sustainable practices in utilizing marine resources, while preserving aspects of their culinary heritage. Collaboration among fishermen, local chefs, and visitors enriches the gastronomic experience and supports the preservation of local culture.Originality/Value - This research highlights the importance of collaboration among communities in creating gastronomic creativity that supports environmental sustainability, the preservation of coastal cultural heritage, and the development of heritage cuisine that remains relevant in the modern era.